Developing of Canva-based learning media to increase student creativity and learning outcomes - Pamulasih Gurning; Elsje Theodora Maasawet; Yusak Hudiyono; Lambang Subagiyo; H. Herliani; A. Akhmad (University of Muhammadiyah Malang, 2024)
The availability of teaching materials at school are still not enough to motivate students to learn because of lack interest, so integration of technology is needed stimulate their motivation. This research aims to develop teaching materials that can be used by teachers and students both within the school and outside the school by developing one of the Canva applications as a media for innovation in a fun learning process. The type of research used is research and development (R&D). The samples in this study were biology teachers and students of State Senior High School 1 of Long Ikis and State Senior High School 2 of Long Ikis. The data analysis technique used to measure the level of creative thinking ability through tests as well as the feasibility, practicality and effectiveness of learning media. The instruments used in this research have been tested for validity and reliability. The results of expert validation of the resulting teaching materials were very good with an average score from 3 validators of 91.15% in the (very valid) category. The teacher's assessment of the practicality of teaching materials showed a result of 91.66% (very practical), while the assessment from students received a score of 93.12% (very practical). The effectiveness of the resulting teaching materials is able to provide an increase in cognitive learning outcomes with a gain score index of 0.74 (high) and learning motivation of 0.75 (high). The results of the effectiveness test using the paired sample t-test show that there is an influence of using Canva media-based teaching materials in improving the biology learning outcomes of students at State Senior High School 1 and 2 of Long Ikis on plant tissue material.